The Effect of Return on Assets and Operating Costs of Operating Income (BOPO) on the Profit Sharing Rate of Mudharabah Deposits At Bank BRI Syariah Period 2017-2020 - Risma Nur’amalia; Fahrul Alam Masruri; Nining Kurniasih (Journal of Business, Accounting and Finance, 2019)
The research method used is the Quantitative method with Multiple Linear Regression model with data processing using SPSS 26. The data used in this study were obtained from the monthly financial statements of BRI Syariah through the website. The results showed that the Return on Assets (ROA) had a partial effect on the Profit Sharing Rate for Mudharabah Deposits, and there was an Operating Cost of Operating Income that had a negative and significant effect on the Profit Sharing Rate for Mudharabah Deposits, and it was proven that the Return on Assets (ROA) and Operating Costs of Income Operational (BOPO) simultaneously affects the rate of profit sharing for mudharabah deposits. It can be concluded that Return on Assets (ROA) has a positive effect on the rate of profit sharing on mudharabah deposits. And the operational cost of operating income has a negative effect on the rate of profit sharing on mudharabah deposits at BRI Syariah Bank. Thus, the management needs to pay attention to the Operational Cost of Operating Income (BOPO) owned